1985
DOI: 10.1128/aem.50.2.207-211.1985
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Drying and Survival of Rhizobium meliloti Strains During Storage at Different Relative Humidities

Abstract: An investigation was made of the survival of six strains of Rhizobium meliloti filtered on membrane filters and held in atmospheres of controlled relative humidities (RH) of from 0 to 100% at 30°C in the presence of air. The rate of water loss in the desiccator was determined by the humidity-controlling solution used. Drying was accelerated by a mild evacuation of the desiccator during the drying step. Survival rates of R. meliloti strains were much higher after slow drying to 0% RH than immediately after rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 23 publications
4
22
1
1
Order By: Relevance
“…To my knowledge, this is the first report of the effects of RH on survival of rhizobia on legume seeds. In spite of the reports by Mary et al (1985Mary et al ( , 1994, the magnitude of the effects reported here was not anticipated. Apparently, hydration of the dry seed coat results in a much more favourable environment for the applied bacteria.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…To my knowledge, this is the first report of the effects of RH on survival of rhizobia on legume seeds. In spite of the reports by Mary et al (1985Mary et al ( , 1994, the magnitude of the effects reported here was not anticipated. Apparently, hydration of the dry seed coat results in a much more favourable environment for the applied bacteria.…”
Section: Discussioncontrasting
confidence: 97%
“…The most comprehensive survey involved only analysis of cell damage, not survival (Bushby and Marshall 1977b). Other reports indicate substantial differences in survival among strains of B. japonicum and Sinorhizobium meliloti applied to membrane filters (Mary et al 1985(Mary et al , 1994. It should be possible to significantly improve survival of inoculant bacteria on soya bean seeds just by selecting strains for tolerance to desiccation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments on the effects of RHs on survival during storage showed that the driest environments led to the greatest survival rates. These results confirm previous works (Mary et al 1985;Mugnier and Jung 1985;Mary et al 1986). The harmful effects of temperature on survival of Rhizobiaceae in the dried state currently described in the literature (Kremer and Peterson 1983;Juwarkar and Rewari 1988;Pesenti-Barili et al 1991) were also observed in this study although satisfactory survival rates were obtained during storage at 3% RH.…”
Section: Nodulation and Nitrogen Fixation By Spray-dried Bradyrhizobisupporting
confidence: 93%